2010
DOI: 10.3184/095422910x12692736419828
|View full text |Cite
|
Sign up to set email alerts
|

Flotation separation of mercury(II) from environmental water samples using thiosemicarbazide derivatives as chelating agents and oleic acid as surfactant

Abstract: A simple and rapid procedure is developed for the quantitative flotation of mercury(II) from aqueous solutions. Thiosemicarbazide derivatives such as: 1-(amino-N-phenylmethanethio)-4-(pyridine-2-yl)thiosemicarbazide (H 2 PPS), N-phenyl-2-(pyridine-2-ylcarbamothioyl) hydrazinecarboxamide (H 2 PBO), 1-(amino(thioformyl)-N-phenylform)-4-(pyridine-2-yl)thiosemicarbazide (H 2 APO), and 1-(amino-N-(pyridine-3-yl)methanethio)-4-(pyridine-2-yl)thiosemicarbazide (H 2 PPY) are used as organic chelating agents and oleic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The important peaks of 13 C NMR of ligands and its diamagnetic complexes are listed in Table 3. From the 13…”
Section: Nmr Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The important peaks of 13 C NMR of ligands and its diamagnetic complexes are listed in Table 3. From the 13…”
Section: Nmr Studiesmentioning
confidence: 99%
“…Their metal complexes have attracted considerable attention which can introduce novel reactivity and frequently stabilize the metal cluster framework [6][7][8][9]. As an extension of our study on thiosemicarbazide moiety [10][11][12][13], we report herein the preparation of Cd (II) and Hg (II) complexes derived from a new thiosemicarbazide, namely 2-amino-4-yl acetothiosemicarbazide ending by ethyl (H2TAET) and allyl (H2TAAT) groups. The study determined the structure of ligands and complexes by traditional techniques and conceded by molecular modelling, DFT calculations and their thermal degradation kinetics using Coats-Redfern and Horowitz-Metzger techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrazones have attracted great and continuous interest, due to their simple synthetic methods, easy complexation with different metal ions as well as their diverse applications. Hydrazones are employed in the extraction of some metal ions in various buffers, [1,2] determination of Ti in bauxite, Portland cement, and amphibolites. [3] In addition, they are utilized as herbicides, insecticides, and plant growth controllers [4,5] as well as catalytic, analytical, and biological applications.…”
Section: Introductionmentioning
confidence: 99%
“…Metal complexes of biogenic ligands have various applications in solution chemistry, and remain to be hot research themes for many researchers [1][2][3][4][5][6][7][8]. Mononuclear binary complexes involving interaction of single metal with one ligand and mixed ligand complexes that contain more than one ligand have been studied for long time [9,10]. The stabilities of the synthesized complexes are a direct function of many factors such as: dielectric constants [11][12][13][14][15][16], stacking interactions between ligands, and metal-ligands [13][14][15][16][17][18], and electrostatic and non-electrostatic interactions [7,9,[11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also revealed that Phen forms both binary and mixed ligand complexes with a number of metal ions in wide pH ranges [6,[19][20][21][22]. It is capable of forming stable metal complexes of even lower oxidation states [10,23,24] in mixed ligand system.…”
Section: Introductionmentioning
confidence: 99%